Analysis of Success Factors And Challenges in Devel-Opment Southeast Asian Community-Based Halal Tourism Destination - Febriyanti, Riri Eriska; Adinugraha, Hendri Hermawan (Jurnal Ekonomi : Journal of Economic, 2026)
The halal tourism industry has shown significant growth acceleration and has become one of the strategic sectors in the global economy. The Southeast Asian region occupies an important position in this development, supported by a rich cultural heritage, the dominance of the Muslim population, and progressive economic dynamics. This study aims to examine in depth the key success factors and challenges in the development of community-based halal tourism destinations in the region. The research was conducted using an exploratory qualitative approach through a cross-country literature study covering Indonesia, Malaysia and Thailand by applying thematic analysis to relevant academic sources, policy documents and case studies.The research findings indicate that the success of halal destination development is strongly influenced by the active participation of local communities, government policy support, and the availability of adequate halal infrastructure. On the other hand, the challenges faced include limited human resource capacity, financial constraints, resistance to cultural change, and misalignment of halal regulations between countries. Based on the analysis, it is concluded that the strategies of community empowerment, infrastructure quality improvement, and regional policy harmonization are crucial steps in building inclusive, competitive, and sustainable community-based halal tourism destinations in Southeast Asia.